Narrative Inquiry: An Alternative Tool to Recapitulate Teachers’ Pedagogical Capital - Bastola, Ganesh Kumar (Dristikon: A Multidisciplinary Journal, 2022)
In this paper, I examine how the interpretative prototype is undertaking its supremacy in the educational research model and how a narrative inquiry paradigm supported and helped me to explore different realities of teachers' pedagogical capital in the context of Nepal. It aims to relate how the perceptions of pedagogical capital affect teachers’ performance in the language classroom. Data for this study were collected from three participants purposively. The data, in this research, have been analyzed based on the framework of Stake (1995). The study uses Bourdieu's (1977) notion of cultural capital for theoretical substantiation and the findings indicate that teachers' pedagogic capital is an ability that can be employed for an effective teaching-learning process. More specifically, this paper pinpoints how narrative inquiry could be considered as an alternative tool to recapitulate teachers' pedagogical capital in educational research.